Influence of Socio Demography Factors on Knowledge of Intimate Partner Violence among Soldiers in Ibadan: A Cross Sectional Survey - Olasupo, Tayo Saidu; Kazeem, Olalekan Taoreed; Akande, Tanimola Makanjuola; Salaudeen, Adekunle Ganiyu; Hussain, Nurudeen Ayoola (Advances in Social Sciences Research Journal, 2018)
The global dimensions of intimate partner violence are alarming. It occurs in all parts of society, regardless of geographic location, socio-economic status, age, cultural and ethnic background, or religious belief, and it’s often devastating effects -psychological, social and economic, short-term and long-term — rebound on families, children, and the community as a whole. This study investigated influence of socio demography factors on knowledge of intimate partner violence among soldiers in Ibadan. Prevalence of knowledge of IPV was also examined. The non experimental study adopted cross sectional design. A total of 26- item carefully structured self report questionnaire was administered to three hundred and fifty-five (N=355) purposively selected married soldiers from Adekunle Fajuyi cantonment, Ibadan, out of which 294 (82.8%) were male and 61 (17.2%) were female. All the respondents (100%) completed at least secondary school education. It was found that prevalence of knowledge of IPV was 192(54.5%). Age of the participants was more on knowledge of IPV than Spouse’s age, years in marriage and educational qualification. Soldiers’ rank did not have significant influence on knowledge of intimate partner violence (IPV) (F(16 339)=.584; P>.05). Male are more on knowledge of IPV than female (t (353) =3.21; P<.05). Type of marriage did not have significant influence on knowledge of intimate partner violence (F(4, 350)=1.384; P>.05). There is need for proactive action on sensitization on intimate partner violence in the Nigerian military.